Computer visual inspection of pear quality - Ilchuk, Mykhailo; Stadnyk, Andrii (Видавництво Львівської політехніки, 2023)
A brief description of the basic stages of image processing is given to pay attention to the segmentation stage as a possible way to improve efficiency in decision-making. The main characteristics of the presented model are visual signs, such as color, shape, the presence of a stem, and others. Due to the different approaches in image processing, a high level of truthfulness is achieved, which is expressed in the percentage ratio of the accuracy of decision-making and varies in the range from 90 to 96%. Therefore, the results obtained in this work make it possible to automate the process of visual inspection with the prospect of increasing the speed and quality of product sales for the consumer.
Keywords: Quality control; Computer vision; Automation